(untitled) (International Journal of Irrigation and Water Management, 2018)
Irrigated agriculture accounts for almost 30% of total crop production and is the single largest user of water in South Africa. The country is water-scarce, and, although water consumption through irrigation has decreased from 80 to about 50% over the past 25 years, the need to improve water use efficiency in irrigation farming is more imperative than ever. Generally, smallholder irrigation schemes (SIS) in South Africa have performed poorly and have not delivered on their development objectives of increasing crop production and improving rural livelihoods. The poor performance of many SIS in terms of productivity and economic impact has been largely attributed to socio-economic, political, climatic, edaphic and design factors, as well as lack of farmer participation. Research and expenditure has tended to concentrate on rehabilitation of irrigation infrastructure, but evidence indicate low yield levels and limited knowledge of crop production among farmers as probably the main reasons for the failure of many SIS in South Africa. The tendency to focus on infrastructure has often yielded little and proved to be fruitless because the human capital was not developed to effectively utilise and maintain the infrastructure. This indicates that farmer practice may actually be constraining performance in spite of the state of irrigation infrastructure. It is therefore recommended that crop production approaches including farmer training be considered alongside all other issues during revitalisation of SIS to improve on performance.